Effects of oral vitamin E and/or selenium on alkaline phosphatase activity in the liver, kidneys and heart of prednisolone-injected rats - Erişir, Mine; Beytut, Ebru; Aksakal, Mesut; Seyran, Ayşe (Veteriner Fakultesi Dergisi, 2010)
The effects of dietary intake vitamin E and Se on alkaline phosphatase (ALP) activity in rats treated with high doses of prednisolone were investigated. 210 rats were divided into five groups (50 rats per groups, except for the first group with 10 rats). The rats were fed a normal diet, but groups 3, 4, and 5 received a daily supplement with oral gavage the 20 mg vitamin E, 0.3 mg Se, and a combination of vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control group (group 1) was given a placebo, and the remaining 4 groups (groups 2, 3, 4, and 5) were injected intramuscularly with 100 mg kg-1 body weight prednisolone. After the last administration of prednisolone, 10 rats from each of the groups other than the control were killed at 4, 8, 12, 24, and 48h and the activity ALP enzyme in the liver, kidneys and heart was measured. In the group treated with prednisolone alone, ALP activity in the liver was significantly increased between 4 and 24 h, in the heart were significantly decreased. ALP activity in the kidneys was not affected by prednisolone. Compared to the control and prednisolone groups, ALP activity in the liver and kidneys of the vitamin E supplemented groups was found to be increased at all time periods. Compared to the prednisolone group, ALP activity in the heart was significantly increased in the vitamin E administered group between 4 and 12 h, recovered to the control level at 24 and 48 h. Compared to the prednisolone groups, ALP activity in the liver was decreased significantly in the Se administered group after 4 h. The increment in the liver ALP activity induced by prednisolone was reduced by Se supplementation. But compared to both the control and prednisolone groups, the ALP activity was significantly decreased in the Se administered group at 24 and 48 h. ALP activity in the kidneys was not affected by Se supplementation. Compared to both the control and prednisolone groups, ALP activity in the heart was decreased in the Se administered group at all time periods. No significant differences were found at any time period in the liver and kidneys ALP activity in the combination group compared to the control. Compared to both the control and prednisolone groups, ALP activity in the heart was significantly decreased in the combination group. The present study demonstrates that in rats treated with prednisolone, generally, vitamin E supplementation increases ALP activity, but Se supplementation decreases. Therefore, vitamin E supplementation may prevent the decreases in ALP activity, Se supplementation may prevent the increases.
Yüksek doz prednizolon enjekte edilmiş ratların karaci?er, böbrek ve kalp alkalin fosfataz aktivitesi üzerine oral vitamin E ve/veya selenyumun etkisi
Keywords: Alkaline phosphatase; Prednisolone; Rat; Selenium; Vitamin E